SEROTYPE CHARACTERISTIC OF PNEUMOCOCCI ISOLATED FROM PATIENTS WITH PNEUMOCOCCAL MENINGITIS - I. S. Koroleva; G. V. Beloshitsky; K. O. Mironov (Вопросы современной педиатрии)
As it was reported by World Health Organization, the annual number of deaths caused by pneumococci reaches 1,6 million people including 700 thousand of children of 0–5 years old. Pneumococcal meningitis is one of the most severe manifestations of pneumococcal infection. S. pneumoniae keeps one of the leading positions in aetiological structure of bacterial meningitis. Data on serotypes distribution of pneumococci in children of the early age in the Russian Federation are limited. In this study serotypes of pneumococci from pediatric patients with pneumococcal meningitis (children aged 0–7 years, n =35) isolated in 1981–2010 in Moscow were identified. Screening for sensitivity of strains to penicillin was performed, as well as molecular typing by MLST approach. The most frequent serotypes causing pneumococcal meningitis in children aged 0–7 years were 19F, 7F, 14 and 1. Most of MDR-strains were collected in 2007–2009. Among MDR-strains and those demonstrating increased resistance to antibiotics, several new allelic patterns were described.